KESADARAN HUKUM PEKERJA MUSIK KOTA SERANG TERHADAP HAK CIPTA MUSIK DITINJAU DARI UNDANG-UNDANG NO. 28 TAHUN 2014 TENTANG HAK CIPTA - Rohmatulloh Rohmatulloh; Anton Aulawi; Alamsyah Basri (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2022)
ABSTRACT An understanding of copyright is a must-have for every music worker or person in the music industry, because this is closely related to the protection of every work created by musicians so that they are not misused by irresponsible parties and take good profits. financially and existentially. This study aims to determine the awareness of musicians related to Law Number 28 of 2014 Year concerning Copyright and the occurrence of copyright infringement, especially song copyrights in Serang City. The research method used is research with a qualitative approach with data collection techniques, namely observation, interviews and documentation. The results of the study indicate that the influence of the Copyright Law for music workers in Serang City who are members of the Salbai 34 Venue community has not had a significant influence in providing legal protection, because in each of their published musical works, almost on average they have not met to get royalties. per month due to several digital platform rules that put limits on getting royalties from each work that is played and there are still many copyright infringement cases, by unscrupulous music workers, both by musicians and content creators. The level of legal awareness of music workers in Serang City regarding copyright in terms of Law Number 28 of 2014 Year is not yet or still lacks legal awareness. There are four indicators to determine that music workers in Serang City do not yet have good legal awareness, where each of these indicators is a stage for the next stage, namely legal knowledge, legal understanding, legal attitudes, and patterns of understanding community behavior.